Producto hipermedial sobre “el ajedrez como herramienta de aprendizaje y comunicación - Nuñez Garcia, Eyleen (2017)
This product has as its starting point the postulates of the educommunication for which an interactive product is presented which raises different dialogical and communication tools, using chess as a learning technique, projecting a suitable virtual space for the construction of knowledge and the Development of logical capacities. It is fundamental to revolutionize education and knowledge, to transmit the need for empirical and collaborative learning, the essence of the project proposal, which through dialogical tools of virtual interaction and self-management provides the individual with the need to get involved and collaborate in this process of learning in a playful way having allies to the sport science. This project aims to be a dialogical space that allows to strengthen the capacities that each individual possesses and to discover their best qualities and abilities, allowing the communication, collaboration, creativity, self-management and reproduction of contents, with the help of “web 2.0” and its main interactive tools. Achieving to disseminate the product and promote chess with the intention of massing it can be a great help for future education processes in the city of Quito, that is why the website tries to rediscover methodologies and learning techniques valid for other fields Education.